Tolerance testing of passive radio frequency identification tags for solvent, temperature, and pressure conditions encountered in an anatomic pathology or biorepository setting - Alina A Leung; Jerry J Lou; Sergey Mareninov; Steven S Silver; Mark J Routbort; Michael Riben; Gary Andrechak; William H Yong (Elsevier, 2010)
Background: Radio frequency identification (RFID) tags have potential for use in identifying and tracking biospecimens in anatomic pathology and biorepository laboratories. However, there is little to no data on the tolerance of tags to solutions, solvents, temperatures, and pressures likely to be encountered in the laboratory. The functioning of the Hitachi Mu-chip RFID tag, a candidate for pathology use, was evaluated under such conditions. Methods: The RFID tags were affixed to cryovials containing tissue or media, glass slides, and tissue cassettes. The tags were interrogated for readability before and after each testing condition or cycle. Individual tags were subjected to only one testing condition but for multiple cycles. Testing conditions were: 1) Ten wet autoclave cycles (121˚C, 15 psi); 2) Ten dry autoclave cycles (121˚C, 26 psi); 3) Ten tissue processor cycles; 4) Ten hematoxylin and eosin (H&E) staining cycles; 5) Ten antigen retrieval pressure cooker cycles (125˚C, 15 psi); 6) 75 o C for seven days; 7) 75-59 o C day/night cycles for 7 days; 8) -80 o C, -150 o C, or -196 o C for 12 months; 9) Fifty freeze-thaw cycles (-196 o C to 22 o C). Results: One hundred percent of tags exposed to cold temperatures from -80 to -196 o C (80 tags, 1120 successful reads), high temperatures from 52 to 75 o C (40 tags, 420 reads), H & E staining (20 tags, 200 reads), pressure cooker antigen retrieval (20 tags, 200 reads), and wet autoclaving (20 tags, 200 reads) functioned well throughout and after testing. Of note, all 20 tested tags tolerated 50 freeze-thaw cycles and all 60 tags subjected to sustained freezing temperatures were readable after 1 year. One dry autoclaved tag survived nine cycles but failed after the tenth. The remaining 19 tags were readable after all 10 dry autoclave cycles. One tag failed after the first tissue processing cycle while the remaining 19 tags survived all 10 tissue processing cycles. Conclusions: In this preliminary study, these RFID tags show a high-degree of tolerance to tested solutions, solvents, temperature, and pressure conditions. However, a measurable failure rate is detectable under some circumstances and redundant identification systems such as barcodes may be required with the deployment of RFID systems. We have delineated testing protocols that may be used as a framework for preliminary assessments of candidate RFID tag tolerance to laboratory conditions.